2005
DOI: 10.1097/01.iop.0000179370.96976.ee
|View full text |Cite
|
Sign up to set email alerts
|

Lateral Tarsal Strip and Quickert Sutures for Lower Eyelid Entropion

Abstract: A combined lateral tarsal strip and Quickert sutures procedure is effective, simple, and addresses all of the factors that contribute to involutional entropion formation, with a good long-term success rate and cosmetic outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(20 citation statements)
references
References 22 publications
0
17
0
3
Order By: Relevance
“…1 Both horizontal and vertical laxity corrections are recommended for this type of entropion to maximize surgical success. [25][26][27][28] There are several limitations to this study. [25][26][27][28] There are several limitations to this study.…”
Section: Summary Of Patient Data and Pinch Test Resultsmentioning
confidence: 99%
“…1 Both horizontal and vertical laxity corrections are recommended for this type of entropion to maximize surgical success. [25][26][27][28] There are several limitations to this study. [25][26][27][28] There are several limitations to this study.…”
Section: Summary Of Patient Data and Pinch Test Resultsmentioning
confidence: 99%
“…López-García et al [7] reported recurrence rate of 17.4% after conventional tarsal strip surgery for involutional entropion. It can be combined with other procedures such as everting sutures [13, 14, 17] and inferior retractor plication, shortening or advancement [12, 18, 19]. There is a range of recurrence rates with such combined procedures.…”
Section: Discussionmentioning
confidence: 99%
“…The combined procedure including LTS, inferior retractor tightening and everting sutures described by Serin et al had 2.2% recurrence rate [12]. Ho et al [14] reported a recurrence rate of 9.4% in primary cases and 22.2% after failed previous procedure after lateral tarsal strip and Quickert sutures for lower eyelid entropion. Allen et al [23] described a modified Quickert and Jones technique which included wedge resection of the eyelid.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 Various techniques have been described for correcting involutional entropions. [5][6][7][8][9][10][11][12][13][14][15][16] Most of these techniques are based on a canthotomy with horizontal tightening of the lower lid using a lateral tarsal strip anchored to the exposed orbital rim with several stitches.…”
mentioning
confidence: 99%